Remotely assessing tephra fall building damage and vulnerability : Kelud Volcano, Indonesia - Williams, George Thomas (2021)
Tephra from large explosive eruptions can cause damage to buildings over wide geographical areas, creating a variety of issues for post-eruption recovery. This means that evaluating the extent and nature of likely building damage from future eruptions is an important aspect of volcanic risk assessment. However, our ability to make accurate assessments is currently limited by poor characterisation of how buildings perform under varying tephra loads. This study presents a method to remotely assess building damage to increase the quantity of data available for developing new tephra fall building vulnerability models. Given the large number of damaged buildings and the high potential for loss in future eruptions, we use the Kelud 2014 eruption as a case study. A total of 1154 buildings affected by falls 1–10 cm thick were assessed, with 790 showing signs that they sustained damage in the time between pre- and post-eruption satellite image acquisitions. Only 27 of the buildings surveyed appear to have experienced severe roof or building collapse. Damage was more commonly characterised by collapse of roof overhangs and verandas or damage that required roof cladding replacement. To estimate tephra loads received by each building we used Tephra2 inversion and interpolation of hand-contoured isopachs on the same set of deposit measurements. Combining tephra loads from both methods with our damage assessment, we develop the first sets of tephra fall fragility curves that consider damage severities lower than severe roof collapse. Weighted prediction accuracies are calculated for the curves using K-fold cross validation, with scores between 0.68 and 0.75 comparable to those for fragility curves developed for other natural hazards. Remote assessment of tephra fall building damage is highly complementary to traditional field-based surveying and both approaches should ideally be adopted to improve our understanding of tephra fall impacts following future damaging eruptions.